Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1073/pnas.1308816110
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine-mediated circuit mechanism underlying controlled appetite for palatable food in Drosophila

Abstract: The easy accessibility of energy-rich palatable food makes it difficult to resist food temptation. Drosophila larvae are surrounded by sugar-rich food most of their lives, raising the question of how these animals modulate food-seeking behaviors in tune with physiological needs. Here we describe a circuit mechanism defined by neurons expressing tdc2-Gal4 (a tyrosine decarboxylase 2 promoter-directed driver) that selectively drives a distinct foraging strategy in food-deprived larvae. Stimulation of this otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…The Tdc2 promoter sequence utilized in this construct has been characterized to drive specific expression in the larval OA neurons21819. Whereas control larvae preferred cooler temperature, transgenic larvae carrying the Tdc2-dTrpA1 construct showed positive thermotactic response when assayed on a 21–28°C temperature gradient (Figure 2 and Supplemental Movies 1, 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tdc2 promoter sequence utilized in this construct has been characterized to drive specific expression in the larval OA neurons21819. Whereas control larvae preferred cooler temperature, transgenic larvae carrying the Tdc2-dTrpA1 construct showed positive thermotactic response when assayed on a 21–28°C temperature gradient (Figure 2 and Supplemental Movies 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic sequence containing a region from -3459 to +4530 of the dTdc2 locus was amplified through stepwise PCR and cloned into pCaSpeR4. Previous studies21819 demonstrated that this element drives specific expression in the larval OA neurons. A 3.6 kb DNA fragment containing the coding region of dTrpA110 (gift from Paul Garrity) tagged with HA was inserted upstream of the dTdc2 coding sequence17.…”
Section: Methodsmentioning
confidence: 97%
“…Here we demonstrate that specifically activating octopaminergic neurons using a bacterial sodium channel is sufficient to induce hyperphagia (see figure 4C and 4D). Also, a recent study demonstrated that octopamine signaling induced fervent feeding behavior when larvae were presented with palatable food [13]. Furthermore, it was shown that Dsk is necessary to inhibit well-fed larvae or adults from eating less palatable foods [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we sought to determine whether Drk is required for ARM within the MBs or other adult brain structures. MB-specific Drk abrogation was achieved with transgenes (drkR-1.2), shown to effectively knock down its levels (17,20) via RNA-mediated interference (RNAi).…”
Section: E0amentioning
confidence: 99%